Process optimization and drying characteristics of instant noodles mixed with potato and oat - HUO Rui; KANG Lianhe; ZHANG Zhifen; QIAO Jianmin; ZHANG Yuanyuan (Shipin yu jixie)
Objective: This study aimed to prepare a nutritious instant noodle with regional characteristics. Methods: The process was optimized using whole potato flour, oat flour, and wheat gluten flour as the basic ingredients. The sensory score, breakage rate, rehydration rate, texture characteristics and hot air-drying characteristics were measured. Results: The optimum process parameters for the potato-oatmeal noodles were as follows: 53% water addition, mixing for 10 min, maturing for 40 min and steaming for 12 min. Based on the drying model, the optimum drying conditions were determined to be 40 min at 90 ℃. Conclusion: The potato-oat instant noodles prepared under the above optimal process conditions are shiny and elastic, soft and firm without sticking to the teeth and have a good taste.